Observations of Lightning NOx Production From Tropospheric Monitoring Instrument Case Studies Over the United States. Issue 10 (14th May 2021) - Allen, Dale; Pickering, Kenneth E.; Bucsela, Eric; Van Geffen, Jos; Lapierre, Jeff; Koshak, William; Eskes, Henk
Abstract: Nitrogen oxides produced by lightning (LNOx ) play an important role in determining mid‐ and upper‐tropospheric concentrations of the hydroxyl radical (OH), methane (CH4 ), and ozone (O3 ). The moles of NOx produced per flash was examined using nitrogen dioxide (NO2 ) columns and cloud properties from the Tropospheric Monitoring Instrument (TROPOMI) and flash counts from the Geostationary Lightning Mapper (GLM) aboard the Geostationary Operational Environmental Satellite‐16 (GOES‐16) and Earth Networks Total Lightning Network (ENTLN) for 29 convective systems over the United States that occurred during 2018 and 2019. For each of the case studies, the LNOx production efficiency (PE) was estimated using TROPOMI pixels over deep convection. First, the NOx columns associated with the TROPOMI NO2 columns were estimated using a specially derived air mass factor (AMF). The tropospheric column due to recent lightning was then determined by subtracting from the median NOx column a background representative of the NOx column due to sources other than recent lightning. Then, the PE was calculated by multiplying the LNOx column by the storm area and dividing by the number of flashes contributing to the column. For a three‐hour chemical lifetime, the mean PE was found to be 175 ± 100 mol per flash for optical flashes from GLM and 120 ± 65 mol per flash for radio‐wave‐detected flashes from ENTLN. The uncertainty associated with these values is mostly due to uncertainties in tropospheric background, AMF, and detection efficiency. GLM PE for individual systems was found to be positively correlated with optical energy. Plain Language Summary: Lightning produces nitrogen oxides (NOx ) as the extreme temperatures within lightning channels break apart molecular nitrogen (N2 ) and oxygen (O2 ). NOx produced by lightning (LNOx ) plays an important role in determining mid‐ and upper‐tropospheric concentrations of the hydroxyl radical (OH), the atmosphere's cleanser; methane (CH4 ), an especially potent greenhouse gas; and ozone (O3 ), a greenhouse gas and pollutant. In this study, NOx production per lightning flash was examined for 29 convective systems over the eastern‐ and central‐ United States that occurred during the warm seasons of 2018 and 2019 using nitrogen dioxide (NO2 ) retrievals and cloud properties from the Tropospheric Monitoring Instrument (TROPOMI) aboard the Copernicus Sentinel‐5 Precursor satellite and lightning flash counts from a satellite‐based Geostationary Lightning Mapper (GLM) and the ground‐based Earth Networks Total Lightning Network (ENTLN). The mean moles of NOx produced per flash was found to equal ∼180 moles per flash for optically detected flashes from GLM and ∼120 moles per flash for radio‐signal‐detected flashes from ENTLN. These values are on the lower end of the commonly cited range of 100–500 moles per flash for midlatitude flashes. Key Points: NO2 columns from Tropospheric Monitoring Instrument (TROPOMI) are used to estimate NOx production per flash Mean NOx production by optically detected lightning flashes equals 175 ± 100 mol per flash for 29 case studies over the United States Mean NOx production by radio‐signal‐detected lightning flashes equals 120 ± 65 mol per flash for 29 case studies over the United States